2020
DOI: 10.1002/ajmg.a.62013
|View full text |Cite
|
Sign up to set email alerts
|

Ciliopathies: Coloring outside of the lines

Abstract: Ciliopathy syndromes are a diverse spectrum of disease characterized by a combination of cystic kidney disease, hepatobiliary disease, retinopathy, skeletal dysplasia, developmental delay, and brain malformations. Though generally divided into distinct disease categories based on the pattern of system involvement, ciliopathy syndromes are known to display certain phenotypic overlap. We performed next‐generation sequencing panel testing, clinical exome sequencing, and research‐based exome sequencing reanalysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…The p.Leu4239Arg variant was previously reported to be associated with Jeune syndrome [ 12 ]. Meanwhile, p.Ile2430Thr is located in the AAA3 nucleotide-binding pocket (amino acids 2251–2505) of the DYNC2H1 protein hexomeric ring-like ATP-hydrolysing motor domain ( , accessed on 2 March 2022) in close proximity with three known Jeune syndrome-associated variants, including p.Ser2423Tyr [ 16 ], described also as “pathogenic” in the ClinVar database ( , accessed on 2 March 2022), and p.Arg2426Cys [ 17 ] and p.Arg2426Leu [ 16 , 18 ]. Thus, taking into account the abovementioned facts, we consider both identified DYNC2H1 p.Ile2430Thr and p.Leu4239Arg variants as pathogenic and causative.…”
Section: Discussionmentioning
confidence: 99%
“…The p.Leu4239Arg variant was previously reported to be associated with Jeune syndrome [ 12 ]. Meanwhile, p.Ile2430Thr is located in the AAA3 nucleotide-binding pocket (amino acids 2251–2505) of the DYNC2H1 protein hexomeric ring-like ATP-hydrolysing motor domain ( , accessed on 2 March 2022) in close proximity with three known Jeune syndrome-associated variants, including p.Ser2423Tyr [ 16 ], described also as “pathogenic” in the ClinVar database ( , accessed on 2 March 2022), and p.Arg2426Cys [ 17 ] and p.Arg2426Leu [ 16 , 18 ]. Thus, taking into account the abovementioned facts, we consider both identified DYNC2H1 p.Ile2430Thr and p.Leu4239Arg variants as pathogenic and causative.…”
Section: Discussionmentioning
confidence: 99%
“…SNVs and small indels were analyzed similarly as exome data with additional emphasis on regulatory variants by using the prediction scores by ANNOVAR. Further variant prioritization was performed with GDCross (Strong et al, 2021), which has incorporated ENCODE, GWAS, signaling pathways, and protein interactions to prioritize noncoding variants. Structural variations (SVs) were generated with three algorithms (Manta, Lumpy, and Wham) and annotated with SnpEff.…”
Section: Methodsmentioning
confidence: 99%
“…In one recent study, scientists did WGS on 4 children with suspected ciliopathies. (Strong et al 2021) The authors identified that all 4 children had mutations in cilia genes, but two patients had additional pathogenic variants for non-coding regions that are associated with liver disease.…”
Section: Is Whole-genome Sequencing More Robust At Diagnosing Ciliopa...mentioning
confidence: 99%